Parallel comparative studies on toxicity of quantum dots synthesized and surface engineered with different methods in vitro and in vivo - Liu F (Dove Medical Press, 2017)
Fengjun Liu1,* Wen Ye1,* Jun Wang2 Fengxiang Song1 Yingsheng Cheng3 Bingbo Zhang21Department of Radiology, Shanghai Public Health Clinical Center, 2Institute of Photomedicine, Shanghai Skin Disease Hospital, The Institute for Biomedical Engineering & Nano Science, Tongji University School of Medicine, 3Department of Radiology, Shanghai Sixth People’s Hospital, Shanghai Jiao Tong University, Shanghai, China *These authors contributed equally to this work Abstract: Quantum dots (QDs) have been considered to be promising probes for biosensing, bioimaging, and diagnosis. However, their toxicity issues caused by heavy metals in QDs remain to be addressed, in particular for their in vivo biomedical applications. In this study, a parallel comparative investigation in vitro and in vivo is presented to disclose the impact of synthetic methods and their following surface modifications on the toxicity of QDs. Cellular assays after exposure to QDs were conducted including cell viability assessment, DNA breakage study in a single cellular level, intracellular reactive oxygen species (ROS) receptor measurement, and transmission electron microscopy to evaluate their toxicity in vitro. Mice experiments after QD administration, including analysis of hemobiological indices, pharmacokinetics, histological examination, and body weight, were further carried out to evaluate their systematic toxicity in vivo. Results show that QDs fabricated by the thermal decomposition approach in organic phase and encapsulated by an amphiphilic polymer (denoted as QDs-1) present the least toxicity in acute damage, compared with those of QDs surface engineered by glutathione-mediated ligand exchange (denoted as QDs-2), and the ones prepared by coprecipitation approach in aqueous phase with mercaptopropionic acid capped (denoted as QDs-3). With the extension of the investigation time of mice respectively injected with QDs, we found that the damage caused by QDs to the organs can be gradually recovered. This parallel comparative investigation suggests that synthetic methods and their resulting surface microenvironment play vital roles in the acute toxicity profiles of QDs. The present study provides updated insights into the fabrication and surface engineering of QDs for their translational applications in theranostics.Keywords: comparative investigation, amphiphilic polymer, glutathione, mercaptopropionic acid, DNA breakage, surface microenvironment